EFFICACY OF INTERMITTENT VACUUM THERAPY AS AN ADJUNCT TO CONVENTIONAL PHYSIOTHERAPY TREATMENT IN PATIENTS WITH KNEE OSTEOARTHRITIS - IRANI, ALI; GERA, KARAN; SAWAL, RADHIKA RAMESH; DOCTOR, ARNAAZ; SINGH, PARVEEN; MEHTA, HARRY (International Journal of Current Pharmaceutical Research, 2024)
Objective: Osteoarthritis (OA) is a severe joint disease that affects more than 60 percent of the elderly. It is highly prevalent and a leading cause of pain and disability worldwide. Symptoms can become increasingly debilitating over time and can greatly affect the quality of life, contributing to feelings of dependence and loss of autonomy in older people. Intermittent vacuum therapy (IVT) is a new technology which is now being used to treat vascular diseases of the legs, to accelerate rehabilitation, to reduce oedema in the lower extremities, to treat cellulite as well as other indications. The majority of the examinations of physiological effects of intermittent vacuum therapy is based on reactions to stable negative pressure in the lower body. Methods: A total of 30 patients, 15 in group A (Conventional) and 15 in group B, were randomly selected based on inclusion and exclusion criteria. Outcome measures-VAS, WOMAC and Knee flexion ROM were assessed pre and post-intervention. The treatment was performed for 10 sessions. Results: There was statistical significance seen in Group A (Conventional) and Group B (Interventional) in all outcome measures. However, treatment with Intermittent Vacuum therapy showed better results in comparison to conventional therapy. Data analysis was done using Paired T test. Conclusion: Intermittent Vacuum Therapy along with conventional protocol showed significant improvement in the above outcome measures in O. A Knee patients. Therefore, Intermittent Vacuum Therapy can be incorporated as a part of rehabilitation in O. A Knee patients.